Continuous Production of Ursodeoxycholic Acid by Using Two Cascade Reactors with Co‐immobilized Enzymes. (24th October 2017) - Zheng, Ming‐Min; Chen, Fei‐Fei; Li, Hao; Li, Chun‐Xiu; Xu, Jian‐He
Abstract: Ursodeoxycholic acid (UDCA) is an effective drug for the treatment of hepatitis. In this study, 7α‐hydroxysteroid dehydrogenase (7α‐HSDH) and lactate dehydrogenase (LDH), as well as 7β‐hydroxysteroid dehydrogenase (7β‐HSDH) and glucose dehydrogenase (GDH), were co‐immobilized onto an epoxy‐functionalized resin (ES‐103) to catalyze the synthesis of UDCA from chenodeoxycholic acid (CDCA). Through optimizing the immobilization pH, time, and loading ratio of enzymes to resin, the specific activities of immobilized LDH‐7αHSDH@ES‐103 and 7βHSDH‐GDH@ES‐103 were 43.2 and 25.8 U g −1, respectively, which were 12‐ and 516‐fold higher than that under the initial immobilization conditions. Continuous production of UDCA from CDCA was subsequently achieved by using immobilized LDH‐7αHSDH@ES‐103 and 7βHSDH‐GDH@ES‐103 in two serial packed‐bed reactors. The yield of UDCA reached nearly 100 % and lasted for at least 12 h in the packed‐bed reactors, which was superior to that of the batchwise reaction. This efficient continuous approach developed herein might provide a feasible route for large‐scale biotransformation of CDCA into UDCA. Abstract : Fixed for function : Four dehydrogenases (7α‐HSDH, LDH, 7β‐HSDH, and GDH) were co‐immobilized pairwise on an epoxy‐functionalized resin. A cascade of two packed‐bed reactors of these co‐immobilized enzymes allow continuous synthesis of ursodeoxycholic acid (UDCA) from the cheap and easily available chenodeoxycholic acid (CDCA).